Curcumin analog, GO‐Y078, overcomes resistance to tumor angiogenesis inhibitors. Issue 10 (16th August 2018) - Shimazu, Kazuhiro; Inoue, Masahiro; Sugiyama, Shunsuke; Fukuda, Koji; Yoshida, Taichi; Taguchi, Daiki; Uehara, Yoshihiko; Kuriyama, Sei; Tanaka, Masamitsu; Miura, Masatomo; Nanjyo, Hiroshi; Iwabuchi, Yoshiharu; et al.
Abstract : Tumor angiogenesis inhibition is one of the most potent strategies in cancer chemotherapy. From past clinical studies, inhibition of the vascular endothelial growth factor pathway successfully treats malignant tumors. However, vascular endothelial growth factor inhibitors alone cannot cure tumors. Moreover, resistance to small molecule inhibitors has also been reported. Herein, we show the antiangiogenic potential of a newly synthesized curcumin analog, GO‐Y078, that possibly functions through inhibition of actin stress fiber formation, resulting in mobility inhibition; this mechanism is different from that of vascular endothelial growth factor inhibition. In addition, we examined the detailed mechanism of action of the antiangiogenesis potential of GO‐Y078 using human umbilical venous epithelial cells resistant to angiogenesis inhibitors (HUVEC‐R). GO‐Y078 inhibited the growth and mobility of HUVEC‐R at 0.75 μmol/L concentration. Expression analyses by microarray and RT‐PCR showed that expressions of genes including that of fibronectin 1 were significantly suppressed. Among these genes, fibronectin 1 is abundantly expressed and, therefore, seems to be a good target for GO‐Y078. In a knockdown experiment using Si‐oligo of fibronectin 1 ( FN1 ), FN1 expression was decreased to half of that in mock experiments as well as GO‐Y078. Knockdown of FN1 resulted in the suppression of HUVEC‐R growth at 24 hours after treatment. Fibronectin is a key molecule contributing to angiogenesis that could be inhibited by GO‐Y078. Thus, resistance to vascular endothelial growth factor inhibition can be overcome using GO‐Y078. Abstract : Human umbilical vein endothelial cells HUVECKi2 resistant to angiogenesis inhibitor are mobile in the presence of sorafenib or sunitinib. However, GO‐Y078 can inhibit the mobility of HUVECKi2.